The Use of Flipbook Media in Indonesian Language Learning at SMKN 4 Palangkaraya in 2024 - Ibnu Ramadhan; Alifiah Nurachmana; Paul Diman; Jumadi Jumadi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This study is a development-oriented research focusing on product development. The product in question is a flipchart-based learning media for Indonesian language subjects in vocational high schools (SMK). The development model used is the 4-D instructional design model (define, design, develop, and disseminate). In this study, the types of validity used are content validity and construct validity. Content validity was assessed by Indonesian language teachers at SMKN 4 Palangkaraya, while construct validity was evaluated by expert lecturers/supervisors. The research results concluded that the use of flipbook learning media for Indonesian language learning has a significant relationship, as indicated by a Sig. (2-tailed) value of .000. Additionally, the use of flipbook learning media improved students' learning outcomes, as shown by the increase in the average score from 55.47 to 87.59 in class X DKV I and from 90.29 to 96.29 in class X DKV II.